A protic salt-derived porous carbon for efficient capacitive deionization: Balance between porous structure and chemical composition. (May 2017) - Li, Yang; Shen, Jiaming; Li, Jiansheng; Sun, Xiuyun; Shen, Jinyou; Han, Weiqing; Wang, Lianjun
Abstract: Capacitive deionization (CDI) with high energy efficiency, low cost, and non-secondary pollution is considered an emerging desalination technology. To pursue excellent electrode materials with high electrosorption capacity is highly desired for practical CDI application. In this work, the protic salt-derived porous carbon was synthesized via the direct pyrolysis of the protic salt, i.e., p -phenylenediamine bisulfate ([pPDA][2HSO4 ]), which was obtained by simply neutralizing p -phenylenediamine with sulfuric acid. The resultant carbon materials possessed large specific surface area, high nitrogen doping, good graphitization and large mesopores. These intrinsic characteristics endowed protic salt-derived porous carbon with excellent electrochemical properties and CDI desalination performance. Particularly, the carbon obtained at 900 °C (C-9) with optimal porous structure (1082 m 2 g −1 ) and chemical composition (5.2% N) exhibited the best electrochemical property with a specific capacitance of 222.3 F g −1 . The CDI results showed that C-9 had a high electrosorption capacity of 16.5 mg g −1 in 100 mg L −1 NaCl solution and excellent electrosorption stability over 20 times of adsorption-desorption cycles. Furthermore, we demonstrated the dependence of CDI performance on the balance between porous structure and chemical composition. These results imply that the protic salt-derived porous carbon should be a promising electrode material for CDI application. Graphical abstract: